Prison Environment and Typology to Support Prisoner Reintegration - Mohamed, Wan Srihani Wan; Hwong, Wen Jie (MAJ - Malaysia Architectural Journal, 2022)
The role of correctional center or known as prison changes over times as philosophies of punishment evolves. Nowadays, the purpose of correctional center focus on rehabilitates and reintegration of prisoner. There is a sign of rising rates of criminal recidivism around the world in recent years. The living condition of prisoner and solitary confinement has caused negative psychological effects and difficulty to reintegrate into society. In relation to that, there is a lack of correctional center environment and typology standard references to support prisoner reintegration. Therefore, this research will focus on prison architectural typology to facilitate the rehabilitation of prisoners to support. In this research, case study will be used as the research inquiry. Therefore, this research will focus on correctional center environment and typology to facilitate the rehabilitation of prisoners to support reintegration.